2021
DOI: 10.5194/acp-21-5549-2021
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric conditions and composition that influence PM<sub>2.5</sub> oxidative potential in Beijing, China

Abstract: Abstract. Epidemiological studies have consistently linked exposure to PM2.5 with adverse health effects. The oxidative potential (OP) of aerosol particles has been widely suggested as a measure of their potential toxicity. Several acellular chemical assays are now readily employed to measure OP; however, uncertainty remains regarding the atmospheric conditions and specific chemical components of PM2.5 that drive OP. A limited number of studies have simultaneously utilised multiple OP assays with a wide range … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 137 publications
(301 reference statements)
5
34
1
Order By: Relevance
“…The intrinsic OP (OP m ) at Delhi ranged from 2 to 99 pmol·min –1 ·μg –1 (average 19.3 ± 12.1 pmol·min –1 ·μg –1 ). This range of OP m is similar to the OP m measured at Lahore (18.9 ± 10.5 pmol·min –1 ·μg –1 ) and Peshawar (27.7 ± 12.1 pmol·min –1 ·μg –1 ), Pakistan, and many North American cities [California (27 ± 4 pmol·min –1 ·μg –1 ), Chicago (11–22 pmol·min –1 ·μg –1 ), Indianapolis (5–17 pmol·min –1 ·μg –1 ), and Atlanta (24 ± 8 pmol·min –1 ·μg –1 ) but was much lower than the OP m reported in the studies conducted in Beijing (average annual OP m = 130 ± 100 pmol·min –1 ·μg –1 and average winter OP m = 37.5 ± 14.4 pmol·min –1 ·μg –1 ). However, it should be noted that all those previous studies reported the OP of PM 2.5 collected using filter sampling followed by water extraction, in contrast to the near real-time measurements of our study that allowed us to capture the diurnal variations in OP while minimizing many of the common sampling artifacts associated with conventional offline OP analysis …”
Section: Resultssupporting
confidence: 80%
“…The intrinsic OP (OP m ) at Delhi ranged from 2 to 99 pmol·min –1 ·μg –1 (average 19.3 ± 12.1 pmol·min –1 ·μg –1 ). This range of OP m is similar to the OP m measured at Lahore (18.9 ± 10.5 pmol·min –1 ·μg –1 ) and Peshawar (27.7 ± 12.1 pmol·min –1 ·μg –1 ), Pakistan, and many North American cities [California (27 ± 4 pmol·min –1 ·μg –1 ), Chicago (11–22 pmol·min –1 ·μg –1 ), Indianapolis (5–17 pmol·min –1 ·μg –1 ), and Atlanta (24 ± 8 pmol·min –1 ·μg –1 ) but was much lower than the OP m reported in the studies conducted in Beijing (average annual OP m = 130 ± 100 pmol·min –1 ·μg –1 and average winter OP m = 37.5 ± 14.4 pmol·min –1 ·μg –1 ). However, it should be noted that all those previous studies reported the OP of PM 2.5 collected using filter sampling followed by water extraction, in contrast to the near real-time measurements of our study that allowed us to capture the diurnal variations in OP while minimizing many of the common sampling artifacts associated with conventional offline OP analysis …”
Section: Resultssupporting
confidence: 80%
“…As a result, policy makers and regulators have developed PM 2.5 exposure guidelines based on epidemiological estimates of disease burdens from unspeciated PM 2.5 . However, recent work has indicated that PM 2.5 toxicity might vary significantly by aerosol composition and source. More research is thus urgently required to estimate the speciated health burdens of PM 2.5 to accurately inform the next generation of exposure guidelines. The modeled heterogeneity in global PM 2.5 composition in this study indicates that estimates of human health impacts that do not consider PM 2.5 composition may be in considerable error, especially in understudied regions (or under future emission regimes).…”
Section: Resultsmentioning
confidence: 99%
“…68 OP is a simple indicator of PM redox activity but reflects a complicated interplay of particle composition and chemistries that induce oxidative stress by free-radical generation. 69 Several studies have found that the level of OP is more strongly associated with acute cardiovascular end points than PM 2.5 mass concentration, indicating that OP is a more relevant health metric than PM mass. 68,69 Among multiple PM components, water-soluble transition metals, especially Mn and Cu, have been proved to be correlated with aerosol OP.…”
Section: Discussionmentioning
confidence: 99%
“…69 Several studies have found that the level of OP is more strongly associated with acute cardiovascular end points than PM 2.5 mass concentration, indicating that OP is a more relevant health metric than PM mass. 68,69 Among multiple PM components, water-soluble transition metals, especially Mn and Cu, have been proved to be correlated with aerosol OP. 70,71 Third, since only a 24-h exposure time was constraint of this study, the long-term effects of exposure to PM 2.5 and its constituents may exhibit different results than those reported in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation